(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The economic importance of chalcid parasitoids in the regulation of 17 coccoid species in Tiblisi has been established. As a result of previous investigations, it was found that the most significant coccoid pests in Tiblisi were: Planococcus ficus (Signoret), Phenococcus mespili (Signoret), Neoopulvinaria innumerabilis (Rathvon), Coccus pseudomagnoliarum (Kuwana), Parthenolecanium corni (Bouché), Ceroplastes japonicus Green, Leucaspis pusilla Löew and Parlatoria oleae Colvée. Parasitoids play an important role in the suppression of the populations of some coccoids and include such chalcids as Microterys clauseni Compére - parasitoid of C. japonicus, Coccobius sp. aff. kurbani Myartseva - parasitoid of Adiscodiaspis tamaricina, Encarsia leucaspidis Mercet - parasitoid of Leucaspis pusilla and L. loewi, Blastothrix longipennis Howard - parasitoid of P. corni, Microterys hortulanus Erdos, Discodes coccophagus (Ratzeburg) and Coccophagus lycimnia (Walker) - all parasitoids of Sphaerolecanium prunastri (Fonscolombe).